Does context matter? Examining robbery reporting in a high crime country - Hernández, Wilson (Criminology & criminal justice, 2023)
Most empirical studies that examine why individuals report property crimes to the police have focused on Global North countries where crime rates are low. This study is situated in the most violent area of the world, Latin America, and examines Peru, which has the highest robbery victimization rate in the Americas. This article examines the applicability of theories of crime reporting in this Global South context using a large sample and multilevel modeling. We find that trust in the police has no impact on the reporting of the robbery of one’s cellphone, purse or wallet. The theories of rational choice and Black’s stratification of law provide strong explanations for the reporting of robbery of these personal items. Individuals of higher social status and those who reside in districts with low levels of social disadvantage are more likely to report, as well as those who have experienced violent victimization.